Pengaruh ESG, Intellectual Capital, dan Leverage terhadap Kinerja Perusahaan (Studi Kasus pada Perusahaan Sektor Infrastruktur yang Terdaftar di BEI Periode 2019-2023) - Rania Haulah; Vicky Dzaky Cahaya Putra (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study was conducted to test and analyze the effect of Environmental Social Governance (ESG), intellectual capital, and leverage on company performance in infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. The performance of companies in this sector shows significant fluctuations due to global uncertainties, such as the Covid-19 pandemic and domestic economic dynamics. The data shows that Return on Assets (ROA) in some companies in this sector tends to be below average, reflecting suboptimal financial performance. The population used in this study was 69 companies. Sampling using purposive sampling technique which resulted in a sample of 11 companies over a five-year period. The data analysis technique used is multiple linear regression analysis using IBM SPSS Statistics 25 software. The test results reveal that partially, ESG and intellectual capital have no significant effect on company performance, while leverage has a significant negative effect on company performance. But together, ESG, intellectual capital, and leverage can affect the performance of companies in the infrastructure sector listed on the IDX in the 2019-2023 period. These findings emphasize the importance of better leverage management as well as optimizing the application of ESG and intellectual capital to improve the competitiveness and sustainability of the company.